Use of platelet-rich plasma in the treatment of deep corneal ulcers induced in rabbits.clinical and histomorphometric evaluation - Donatti, C.; Brandão, C. V S; Ranzani, J. J T; Perches, C. S. [UNESP]; Padovani, C. R. [UNESP]; Pellizzon, C. H. [UNESP]; Sereno, M. G. (FapUNIFESP (SciELO), 2013)
The repair process induced corneal ulcer in rabbits using platelet-rich plasma in the form of eyedrop or clot was clinically evaluated and compared. Sixty rabbits were divided into four groups of 15 animals, denominated platelet group (PG), clot group (CLG), control group (CG), and amniotic control group (AG). Experimental groups were then subdivided into three groups (M4, M7, M30), corresponding to the end of the evaluation period. There were no differences between treatments regarding ocular sensitivity, chemosis and ocular secretion. The groups treated with PRP either as eyedrop or a clot showed less opacity than the animals treated only with amniotic membrane at the moment of the final evaluation. The presence of corneal ulcers in the groups treated with PRP showed lower intensity than the other groups. Histomorphometric examination showed that corneal epithelization in the initial phase of the lesion was greater when using PRP. The use of amniotic membrane promoted corneal epithelial and stromal thickness, as well as synergism when associated to PRP.
Keywords: Cornea; Histomorphometric; Platelet; Rabbit; Ulcer